2000
DOI: 10.1074/jbc.275.18.13888
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the [Fe-S] Cluster-binding Residues of Escherichia coli Biotin Synthase

Abstract: The gene encoding Escherichia coli biotin synthase (bioB) has been expressed as a histidine fusion protein, and the protein was purified in a single step using immobilized metal affinity chromatography. The His 6 -tagged protein was fully functional in in vitro and in vivo biotin production assays. Analysis of all the published bioB sequences identified a number of conserved residues. Single point mutations, to either serine or threonine, were carried out on the four conserved (Cys-53, Cys-57, Cys-60, and Cys-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…The presence of a serine residue as a naturally occurring ligand for a protein bound [4Fe-4S] cluster has not been previously observed, but a serine for cysteine site directed mutation has often been used to modulate or eliminate cluster activity [46][47][48][49][50][51]. Examination of the electron density near the auxiliary cluster ( Figure 3B) shows clear density for the serine ligand (Ser283) with a short Fe-O bond length (1.8 Å in the MTA complex), which likely reflects deprotonation of the serine ligand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a serine residue as a naturally occurring ligand for a protein bound [4Fe-4S] cluster has not been previously observed, but a serine for cysteine site directed mutation has often been used to modulate or eliminate cluster activity [46][47][48][49][50][51]. Examination of the electron density near the auxiliary cluster ( Figure 3B) shows clear density for the serine ligand (Ser283) with a short Fe-O bond length (1.8 Å in the MTA complex), which likely reflects deprotonation of the serine ligand.…”
Section: Discussionmentioning
confidence: 99%
“…This cluster is held in place by three conserved cysteine residues [14] and an unanticipated ligand from close to the C-terminus, Ser283. Serine is previously unreported as a natural ligand for [4Fe-4S] clusters, although this residue has been introduced as a cluster ligand by site directed mutagenesis [46][47][48][49][50][51]. In the TeLipA2:SAH complex structure, the Ser283 alkoxy oxygen atom lies in close proximity to an additional metal atom, which because of its abundance in the crystallization medium (initially approximately 160 mM), has been modeled as a sodium ion (Na-O distance 2.5 Å, Figure 3B).…”
Section: Structure Of Telipa2mentioning
confidence: 99%
“…c Nanomoles of biotin formed/nmol of enzyme monomer (Ϯ0.04) under the conditions of the assay described previously (13). min) photo-illumination process.…”
Section: Adomet Oxidizes the Reduced [4fe-4s] 1ϩ Cluster Of Biob Intomentioning
confidence: 99%
“…Finally, studies of site-directed mutants have demonstrated the requirement of six cysteines for activity. Cys-53, Cys-57, and Cys-60 (numbers referred to the Escherichia coli enzyme) are thought to be important for chelation and function of the [4Fe-4S] cluster (13,15). The function of Cys-97, Cys-128, and Cys-188, which are also absolutely required, is still unknown (24).…”
mentioning
confidence: 99%
“…Indeed, it is evolved to accommodate simultaneously two different oxygen-sensitive clusters, one 2ϩ and one 2ϩ per monomer, with unique roles in catalysis (6). The [4Fe-4S] could be ligated by three cysteines of a CX 3 CX 2 C box, and a fourth, still unidentified ligand (7)(8)(9). More recently, Ugulava et al (10) proposed that the [2Fe-2S] center could be ligated at an alternative site not previously occupied by the [4Fe-4S] center.…”
mentioning
confidence: 99%